1993
DOI: 10.1177/019459989310900103
|View full text |Cite
|
Sign up to set email alerts
|

Mal de debarquement syndrome: A forgotten entity?

Abstract: Mal de debarquement syndrome is defined by a persistent sensation of rocking and swaying commonly felt with sea travel that is first noted on return to land. Mal de debarquement syndrome is not to be confused with seasickness, which causes nausea, vomiting, diaphoresis, and headache. Four female patients with mal de debarquement syndrome are reviewed. Mal de debarquement is normally a short-lived phenomenon. The need for extensive evaluations may be avoided by an awareness of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 4 publications
0
27
0
1
Order By: Relevance
“…Mal de debarquement (MDD) is a common, transient sensation of disequilibrium that is most frequently triggered after disembarking from an oceangoing vessel (1)(2)(3). Literally "the sickness of disembarking," it is a distinct entity from seasickness or other forms of motion sickness in that associated symptoms, such as headache, nausea, and vomiting, are absent (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mal de debarquement (MDD) is a common, transient sensation of disequilibrium that is most frequently triggered after disembarking from an oceangoing vessel (1)(2)(3). Literally "the sickness of disembarking," it is a distinct entity from seasickness or other forms of motion sickness in that associated symptoms, such as headache, nausea, and vomiting, are absent (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Literally "the sickness of disembarking," it is a distinct entity from seasickness or other forms of motion sickness in that associated symptoms, such as headache, nausea, and vomiting, are absent (1,2). The offending sensation-one of still being aboard ship-is only triggered after a return to solid ground, and may actually be relieved by re-boarding the vessel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other conditions resemble PPV: space phobia [18], "Mal de débarquement syndrome" [7,19], and "visual vertigo" [5]. Space phobia, a pseudo-agoraphobic syndrome, describes a fear of absent visuospatial support for balance (open spaces) and of falling.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested dysfunction of the vestibular system by overstimulation [8]. This mechanism, however, seems unlikely for two reasons: Firstly, vestibular function tests are consistently normal in patients with MdD and, secondly, the vestibular system itself cannot prolong vestibular information beyond 2 or 3 minutes, as accomplished by the socalled velocity storage mechanism (which is the one that makes us feel spinning for a while after leaving a carousel).…”
mentioning
confidence: 99%